RELEVANSI ISLAM NUSANTARA SEBAGAI EPISTEMOLOGI PANCASILA Upaya Merangkai Sebab, Menyemai Tanggungjawab - Majid, Mohamad Arif (ASKETIK, 2018)
Abstract Nusantara Islam is ala Indonesian Islam, a combination of theological values of Islam and Local traditions of Nusantara. The characteristics of Nusantara Islam show local wisdom in Nusantara which does not disobey Islamic teaching, yet they synergize it to local customs all over Indonesia. The coming of Islam in Nusantara did not break nor challenge the local traditions but it enriched and simultaneously Islamized them. The constant contact between local traditions and Islamic soul resulted in mutual binding and complement to form an excellent character believed and preserved from generation to generation for centuries. Hence, the value had been so close and attached to Indonesian character. For years such character stayed in the womb of Nusantara Islam and ready to be born, and then Bung Karno together with the nation founding fathers helped the birth of this nation value as the foundation of Indonesian Independence. This was the most wanted Pancasila which is believed now has been left by Indonesians and some faults and deviations on the life of state management and social system occurred. Muslims, therefore, must be responsible for this and take strategic steps at once to face this by carrying out the right and precise Islamic education.